Applying Putnam’s two-level game theory to health diplomacy: South Africa’s domestic and international responses to the COVID-19 pandemic from 2020 to 2023 - Blake, Robin (University of Pretoria, 2026)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2025.